The impact of jurisprudential and legal rules in explaining the provisions of medical calamities - amroun, amel; ben said, moussa (Journal of Social Sciences and Humanities, 2024)
The jurisprudential rules are total and bring together many jurisprudential branches. Due to the large number of calamities, especially medical ones, there has become an urgent need to implement these rules to find solutions and rulings for their branches. Perhaps the most important of them are those related to the medical aspect, so the issue of organ removal and transplantation in general, and kidney removal and transplantation in particular, is considered one of the issues. The most sensitive and widespread topic, as it affects the human soul that God has honored, living and dead, here lies the importance of this research, as the reality of the situation requires us to research this topic, and as for what is related to Algerian law; He addressed the issue of kidney removal and transplantation in accordance with Law 18-11 related to health, as he demonstrated, with his recent amendment to this law, his attempt to agree with Islamic law in this matter.